Hubungan Tingkat Pengetahuan Dengan Ketepatan Penggunaan Obat Pada Swamedikasi Nyeri Sendi - Mexsi Mutia Rissa (Program Studi Farmasi UNAJA, 2022)
Abstract Background: The prevalence according to Basic Health Research data in 2018 states that joint pain problems in Indonesia are 7.3% with a disease ratio of 8.5% in women and 6.1% in men, and the incidence of joint pain problems in Yogyakarta is 5.9 %. Based on the Central Statistics Agency, in 2019 the percentage of the Indonesian population who did self-medication or self-medication was 71.46%. Objective: The purpose of this study was to determine the relationship between the level of knowledge and the accuracy of drug use on joint pain self-medication at the Harapan Sehat Pharmacy for the period of February 2022. Method: The research method used is an analytical observational method with a cross sectional approach, where the researcher makes observations only once at a time. Data collection will be carried out based on a questionnaire that will be distributed to respondents. Data analysis used statistical package for the social science (SPSS) version 25 with chi-square test. Results: The results showed good knowledge of 70 respondents (62%), sufficient knowledge of 22 respondents (20%), and poor knowledge of 20 respondents (18%) with proper use of drugs 104 respondents (93%) and inappropriate use of drugs 8 respondents (7 %). Conclusion: The results of the chi-square test obtained p value = 0.000 <0.05 so it can be concluded that there is a significant relationship between the level of knowledge and the accuracy of drug use.